Instability and nonlinearity in the euro area Phillips curve - Alberto Musso; Livio Stracca; Dick van Dijk (European Central Bank (ECB), 2007)
This paper provides a comprehensive analysis of the functional form of the euro area Phillips curve over the past three decades. In particular, compared to previous literature we analyse the stability of the relationship in detail, especially as regards the possibility of a time-varying mean of inflation. Moreover, we conduct a sensitivity analysis across different measures of economic slack. Our main findings are two. First, there is strong evidence of time variation in the mean and slope of the Phillips curve occurring in the early to mid 1980s, but not in inflation persistence once the mean shift is allowed for. As a result of the structural change, the Phillips curve became flatter around a lower mean of inflation. Second, we find no significant evidence of non-linearity, in particular in relation to the output gap.
Keywords: E52; E58; 330; Asymmetry; inflation; output gap; smooth transition model; Structural change; Phillips-Kurve; Inflationsbekämpfung; Preisrigidität; Strukturwandel; EU-Staaten